Knowledge, Attitude, And Practice Of Dog Ectoparasite Prevention Among Dog Owners In Penang, Malaysia - Ang Hui Qian (2024)
Ectoparasites are a group of parasites that live outside of their host and infestations can lead to several life-threatening diseases in dogs. Thus, ectoparasite preventatives in dogs including collars, palatable tablets, spot-on, and spray are important to minimize the transmission of ectoparasitic diseases in dogs. However, up to now, there is still no available data on the knowledge, attitude, and practice of ectoparasite preventative among dog owners in Penang, Malaysia. Therefore, this study was conducted to determine the knowledge, attitude, and practice of dog ectoparasites prevention, and the associated risk factors, among dog owners in Penang, Malaysia. The study findings showed that dog owners in Penang had a good knowledge (n=75, 68.18%), attitude (n=101, 91.82%), and practice (n=73, 66.36%) towards dog ectoparasite prevention. Besides, the results indicated that age and the highest level of education were the significant factors that impacted the knowledge, attitude, and practice (KAP) of dog ectoparasite prevention among dog owners in Penang, Malaysia. There were no significant associations between other sociodemographic characteristics such as gender, monthly income, district of residence and management of dogs with the KAP results. In conclusion, KAP of dog ectoparasite prevention is influenced by age and highest level of education and this study can benefit the public by allowing more appropriate ways to be implemented to improve owners’ compliance with ectoparasite prevention based on the data collected. Keywords: Dog Ectoparasite Prevention, Dog owners, Knowledge, Attitude and Practice of Dog Owners, Penang, Malaysia